The Effect of Ease of Use Of The Application, Quality Of Service, And Promotion On Repurchase Interest (Grab Application Customer Study at PT Sido Muncul Kebon Jeruk) - Aprileny Imelda; Puspitasari Rianav; Emarawati Jayanti Apri (Indonesia Banking School, 2023)
This study aims to determine and analyze the effect of ease of use of the application, quality of service, and promotion on repurchase interest in consumer studies of Grab application customers. Sido Muncul Kebon Jeruk, West Jakarta. The research method used is a survey method, using a questionnaire as a data collection tool. The population in this study were all employees of PT. Sido Muncul Kebon Jeruk, West Jakarta, with a sample size of 98 respondents. The analysis tool used is SPSS v 25. Based on the results and discussion, it proves that partially ease of use has negative and significant effect on repurchase interest partially service quality has positive and significant effect on repurchase interest, and partially promotion has positive and significant effect on purchase intention. Simultaneously, ease of use, quality of service, and promotion have a significant effect on repurchase interest.